Influence of coal macerals on carbonization process and sodium storage behavior - Rundong HE; Hang GUO; Zhongchao SUN; Wencui LI (Meitan xuebao)
Coal has the advantages of low cost and rich aromatic structure, which makes it a high-quality precursor for the preparation of hard carbon anode materials for sodium-ion batteries. Currently, there has been extensive research on the structural regulation and sodium storage performance optimization of coal-based hard carbon materials. However, the composition of coal is complex, and the mechanism of coal composition on carbon formation and sodium storage behavior is not clear. Based on this, the density gradient centrifuge method is used to enrich the organic maceral in coal with Xinjiang bituminous coal as precursor and different maceral-based hard carbon materials are prepared by acid elution of ash and high temperature carbonization treatment. The study investigated the variations in the pyrolysis process of each maceral and their impacts on the growth of graphite microcrystals, pore structure, and surface elemental composition in hard carbon materials. Furthermore, the discrepancies in sodium storage behavior among hard carbon materials derived from different macerals are explored through galvanostatic charge-discharge, galvanostatic intermittent titration technique, electrochemical impedance spectroscopy, and cyclic voltammetry. The findings indicate disparities in the pyrolysis processes of vitrinite and inertinite. Specifically, inertinite exhibits superior thermal stability compared to vitrinite. Moreover, vitrinite tends to yield graphite microcrystals with larger layer sizes, the graphitization degree of vitrinite-based hard carbon is higher at the same carbonization temperature. Additionally, vitrinite-based hard carbon demonstrates elevated concentrations of oxygen-containing functional groups on its surface in contrast to inertinite-based hard carbon. In terms of sodium storage behavior, the electrochemical properties of vitrinite-based hard carbon and inertinite-based hard carbon showed different changes with the carbonization temperature. Notably, the hard carbon material synthesized through vitrinite carbonized at 1200 ℃ demonstrated the most favorable sodium storage performance, it boasts a high capacity of 305.8 mAh/g at a current density of 0.02 A/g, and a high initial Coulombic efficiency of 82.2% is displayed. It is pointed out that under the current density of 0.2 A/g, the capacity still kept 235.7 mAh/g. The excellent electrochemical properties attributed to its increased interlayer sodium storage sites and concentration of oxygen-containing functional groups.